TO COMPARE DEXMEDETOMIDINE WITH CLONIDINE AS ADJUVANTS TO ROPIVACAINE IN EPIDURAL ANESTHESIA IN PATIENTS UNDERGOING LOWER ABDOMINAL SURGERIES - SAGAR, TAMILISETTI VIDYA; BYNDOOR, YATISH; P, MADHAV (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study is to compare dexmedetomidine with clonidine as adjuvants to ropivacaine in epidural anesthesia in the onset of sensory and motor blockade, duration of post-operative analgesia, level of sedation, and occurrence of side effects. Methods: This study was a prospective randomized observational and comparative study. Sixty patients of age between 20 and 50 years with the American Society of Anesthesiologists grade I and II physical status belonging to both sexes undergoing abdominal surgeries under epidural anesthesia are included; patients were allocated randomly into two groups comprising 30 patients in each group. Group A patients are given injection dexmedetomidine, added to ropivacaine and Group B patients are given injection clonidine, added to ropivacaine by epidural route. Following parameters were observed intra and post-operatively: Onset of sensory and motor blockade and duration of motor blockade, level of sedation, duration of analgesia, and side effects. All data are presented in tabular form as mean ± standard deviation. The analysis is done by unpaired t-test. Statistical analysis is done using SPSS software. Results: Mean time of onset of sensory blockade in Group A was 9.50 min with standard deviation of 1.85 and in Group B was 9.48 min with standard deviation of 1.60. Mean time of onset of motor blockade in Group A was 20.66 min with standard deviation of 2.83 and in Group B was 20.48 min with standard deviation of 2.52. Mean duration of analgesia in Group A was 312.66 min with standard deviation of 22.02 and in Group B was 314.20 min with standard deviation of 24.58. There is no statistical difference between two groups in the level of sedation which was assessed by Wilson’s sedation scale. Side effects most commonly observed are hypotension and bradycardia. Conclusion: We conclude that both dexmedetomidine and clonidine are similar in efficacy and tolerability as adjuvants in the onset of sensory and motor blockade and post-operative analgesia when added to ropivacaine in epidural anesthesia.